THE FEMALE IMAGE AND ITS DRAMATIC FUNCTION IN THE TRAGEDY “GÜZEL HELENA” (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the representation of the female image and its dramatic function in the tragedy “Güzel Helena”. Through literary and structural analysis, the study explores how the character of Helena operates not merely as a symbol of beauty but as a catalyst of conflict, a bearer of ideological meaning, and a reflection of gendered power structures. The paper analyzes Helena’s role in shaping dramatic tension, her symbolic function within the narrative, and her relationship to themes of fate, desire, and political consequence. The findings demonstrate that Helena’s character transcends the stereotype of passive femininity and becomes central to the tragic structure of the work.